PP No. 10 Tahun 1983 dan SE No. 08/SE/1983 tentang Izin perkawinan dan perceraian bagi pegawai negeri sipil serta petunjuk dan pelaksanaan - INDONESI._[UNDANG_UNDANG,_Peraturan_dan_sebagainya] (Yayasan Binadhika, 1991)
us, c.1/ast c.2